Is Rural Nursing a Specialty? - Kathy Crooks (Rural Nurse Organization; Binghamton University, 2004)
Like many other nurses who work in rural and remote areas, I never considered myself a specialist. That is until several years ago when I started to teach an undergraduate course in rural nursing. As I immersed myself in the little bit of rural literature that was available at the time, I recognized that I was becoming increasingly convinced that indeed rural nursing is a specialty. I remember feeling really pleased that finally someone somewhere understood that nursing in rural sites was not merely the poor relation of urban nursing, but something that required special knowledge and skill. From that time to the present, I have proudly pointed out this fact to students. In Canada, however, rural nursing is still struggling to become recognized as a distinct entity. This caused me to consider the obstacles that we still face on the road to specialty status.